Corticosterone analgesia is mediated by the spinal production of neuroactive metabolites that enhance GABAergic inhibitory transmission on dorsal horn rat neurons. (26th November 2014) - Zell, Vivien; Juif, Pierre‐Éric; Hanesch, Ulrike; Poisbeau, Pierrick; Anton, Fernand; Darbon, Pascal
Abstract Corticosterone (CORT) is a glucocorticoid produced by adrenal glands under the control of the hypothalamic–pituitary–adrenal axis. Circulating CORT can enter the central nervous system and be reduced to neuroactive 3α5α‐reduced steroids, which modulate GABAA receptors. In the dorsal spinal cord, GABAergic transmission modulates integration of nociceptive information. It has been shown that enhancing spinal inhibitory transmission alleviates hyperalgesia and allodynia. Therefore, the spinal neuronal network is a pivotal target to counteract pain symptoms. Thus, any increase in spinal 3α5α‐reduced steroid production enhancing GABAergic inhibition should reduce nociceptive message integration and the pain response. Previously, it has been shown that high levels of plasma glucocorticoids give rise to analgesia. However, to our knowledge, nothing has been reported regarding direct non‐genomic modulation of neuronal spinal activity by peripheral CORT. In the present study, we used combined in vivo and in vitro electrophysiology approaches, associated with measurement of nociceptive mechanical sensitivity and plasma CORT level measurement, to assess the impact of circulating CORT on rat nociception. We showed that CORT plasma level elevation produced analgesia via a reduction in C‐fiber‐mediated spinal responses. In the spine, CORT is reduced to the neuroactive metabolite allotetrahydrodeoxycorticosterone, which specifically enhances lamina II GABAergic synaptic transmission. The main consequence is a reduction in lamina II network excitability, reflecting a selective decrease in the processing of nociceptive inputs. The depressed neuronal activity at the spinal level then, in turn, leads to weaker nociceptive message transmission to supraspinal structures and hence to alleviation of pain.